EduHealth Time Application for Enhancing Nutrition and Health Knowledge and Skills among Junior High School Students - Nugroho, Fajar Ari; Kusumastuty, Inggita; Cempaka, Anggun Rindang (SPEKTA (Jurnal Pengabdian Kepada Masyarakat : Teknologi dan Aplikasi), 2025)
Background: Adolescents often acquire health knowledge through traditional education but frequently face challenges in sustaining healthy behaviors due to a range of social, environmental, psychological, and developmental factors. Contribution: We developed "EduHealth Time," an Android application co-designed with educators and health personnel to deliver on-demand health education videos and integrated screening modules (anthropometry, anaemia risk, illness monitoring), with built-in functionality for exporting data to support School Health Unit documentation. Method: A one-group pretest-posttest design was implemented during a community-service pilot at SMPIT As-Salam Malang (October–November 2024), involving 65 junior high school students. The app development followed the Plan–Act–Observe–Reflect cycle. Usability and feasibility were evaluated through a seven-item structured survey. Results: EduHealth Time was made publicly available on Google Play. Usability outcomes were highly positive: 92% of participants reported ease of data entry, 100% experienced no system errors, and 100% completed screening tasks without difficulty. The educational and screening functions were rated feasible by 92% of users. Significant improvements were observed in knowledge scores: +5.2 points for balanced diet, +21.4 points for physical activity, and +7.4 points for reproductive health. Conclusion: The EduHealth Time application is a scalable and contextually relevant mHealth platform that enhances adolescent health knowledge and supports self-monitoring. Its integration of multimedia learning and screening features provides a model for continuous school-based health education.